PERSPEKTIF POLITIK HUKUM TERHADAP TANTANGAN KEBERADAAN HUKUM MENUJU GLOBALISASI - Miftachus Sjuhad (Widya Yuridika, 2018)
In the field of law, globalization is characterized by the borderless states; no state can claim that it follows a system of law absolutely. There have been mixes and penetration between on system of law to another. In this globalization era, any discussions on the challanges of the existence of law have not been separated from the internal influence of the nation and the surrounding political system and also the cultures. This analyse will explore how the internal and external challenges of the law face the globalization currents that demand on perfect preparation in all aspects. The political will of the government of Indonesia is really different between before and after the reformation. Multidimensional cries that have not been finished yet may potentially destroy the nation and state of Indonesia up to the zero point. Meanwhile, on the one hand, from the law point of view, in this country, the political products are full of various interests. On the other hand, the national law of Indonesia is facing globalization. Therefore, it is vital to create a harmonious link between the national law and the international law, with attention given to the internal context of Indonesian people. Kata kunci: Politik hukum, Harmonisasi hukum, globalisasi